An integrated approach to the structural characterization, long-term toxicological and anti-inflammatory evaluation of Pterospermum rubiginosum bark extract. (23rd May 2023) - Anish, Rajamohanan Jalaja; Mohanan, Biji; Aswathy, Thankamani Ravikumar; Nair, Aswathy; Radhakrishnan, K.V.; Rauf, Arun A.
Abstract: Ethnopharmacological relevance of study: Pterospermum rubiginosum is an evergreen plant in Western Ghats, India, used by traditional tribal healers due to its excellent biological potential for treating inflammation and pain relief procedures. The bark extract is also consumed to relieve the inflammatory changes at the bone fractured site. The traditional medicinal plant in India have to be characterized for its diverse phytochemical moieties, its interactive multiple target sites, and to reveal the hidden molecular mechanism behind the biological potency. Aim of the study: The study focussed on plant material characterization, computational analysis (prediction study), toxicological screening (In vivo), and anti-inflammatory evaluation of P. rubiginosum methanolic bark extracts (PRME) in LPS-induced RAW 264.7 cells. Materials and methods: The pure compound isolation of PRME and their biological interactions were used to predict the bioactive components, molecular targets, and molecular pathways of PRME in inhibiting inflammatory mediators. The anti-inflammatory effects of PRME extract were evaluated in the lipopolysaccharide (LPS)-induced RAW264.7 macrophage cell model. The toxicity evaluation of PRME was performed in healthy 30 Sprague–Dawley experimental rats, were randomly divided into five groups for toxicological evaluation for 90 days. The tissue levels of oxidative stress and organ toxicity markers were measured using the ELISA method. Nuclear magnetic resonance spectroscopy (NMR) was performed to characterize the bioactive molecules. Results: Structural characterization revealed the presence of vanillic acid, 4-O-methyl gallic acid, E-resveratrol, gallocatechin, 4′-O-methyl gallocatechin, and catechin. Molecular docking of NF-kB exhibited significant interactions with vanillic acid and 4-O-methyl gallic acid with binding energy −351.159 Kcal/Mol and −326.5505 Kcal/Mol, respectively. The PRME-treated animals showed an increase in total GPx and antioxidant levels (SOD and catalase). Histopathological examination revealed no variation in the liver, renal and splenic tissue's cellular pattern. PRME inhibited the pro-inflammatory parameters (IL-1β, IL-6, and TNF-α) in LPS-induced RAW 264.7 cells. The protein level of TNF-α and NF-kB protein expression study brought out a notable reduction and exhibited a good correlation with the gene expression study. Conclusion: The current study establishes the therapeutic potential of PRME as an effective inhibitory agent against LPS-activated RAW 264.7 cells induced inflammatory mediators. Long-term toxicity evaluation on SD rats confirmed the non-toxic nature of PRME up to 250mg/body weight for 3 months. Graphical abstract: Image 1 Highlights: The phytochemical characterization revealed the presence of vanillic acid, 4-O-methylgallic acid, E-resveratrol, gallocatechin, 4-O-methylgallocatechin, and catechin from PRME. Molecular docking studies confirmed the drugability of phytochemicals isolated from PRME. Molecular docking evaluation of NF-kB exhibited significant interactions with vanillic acid and 4-O-methylgallic acid with remarkable binding energy. Long-term toxicity evaluation on Sprague-Dawley rats confirmed that PRME is non-toxic up to 250mg/body weight for 3 months. The current study establishes the therapeutic potential of PRME as an effective anti-inflammatory agent against LPS-activated RAW 264.7 cells induced inflammatory mediators.